2021
DOI: 10.1177/13623613211019159
|View full text |Cite
|
Sign up to set email alerts
|

Food insecurity in the households of children with autism spectrum disorders and intellectual disabilities in the United States: Analysis of the National Survey of Children’s Health Data 2016–2018

Abstract: Individuals with autism spectrum disorder and co-occurring intellectual disabilities experience substantial challenges in accessing needed supports. This research aimed to understand the prevalence and factors associated with food insecurity among families of children with autism spectrum disorder and co-occurring intellectual disabilities. Utilizing the National Survey of Children’s Health (2016–2018) data, this article illustrated that the households of children with autism spectrum disorder and co-occurring… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 71 publications
0
8
0
Order By: Relevance
“…Prior research based on the analyses of the NSCH data by the authors identified various factors at individual-, family-, and community-levels contributed in predicting higher levels of food insecurity in households of children on the autism spectrum. 5 For example, children on the autism spectrum were more likely to use emergency room services, missed several days of school, and were more likely to be exposed to adverse childhood experiences. These variables also strongly predicted food insecurity in the multivariate regression models.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Prior research based on the analyses of the NSCH data by the authors identified various factors at individual-, family-, and community-levels contributed in predicting higher levels of food insecurity in households of children on the autism spectrum. 5 For example, children on the autism spectrum were more likely to use emergency room services, missed several days of school, and were more likely to be exposed to adverse childhood experiences. These variables also strongly predicted food insecurity in the multivariate regression models.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the [Author’s organization] respondents consisted of a self-selected sample of parents/caregivers of children on autism spectrum. In comparing the distribution of race/ethnicity characteristics of parents/caregivers of children on autism spectrum in the National Survey of Children’s Health data, 38 the [Author’s organization] respondents had higher proportion of NHW and a lower proportion of families that identified themselves as Hispanic. These differences result from self-selection of the survey participants, and the study design limitations make it difficult to compute selection probabilities due to lack of access to respondent background characteristics who got the survey links.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional costs of care, disparate access to needed services, and reduced income from job loss are likely contributing to food insecurity in this population [27]. Children who experience food insu ciency have limited or uncertain ability to acquire acceptable foods [28] suggesting that these children may not always have access to various textures and avors to support developmentally appropriate feeding skills.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, these parents are often engaged in high levels of advocacy on behalf of their children from birth [or receipt of diagnosis; ( 10 )] and persists through adulthood as they advocate for job placements and more ( 11 ). These parents often shoulder additional financial demands surrounding the cost of specialized therapies and health care for their children ( 12 ). Parents of children with neurodevelopmental disabilities may also be required to deal with child challenging behaviors, such as aggression and hyperarousal ( 13 , 14 ), limitations in child adaptive functioning ( 15 17 ), as well as social ( 18 , 19 ) and academic challenges ( 20 , 21 ), all of which can further contribute to higher caregiver burden and stress.…”
Section: Introductionmentioning
confidence: 99%